Search or Scroll: How Credibility versus Likability Premiums Shape Consumers’ Following Decisions - Shalev, Edith; Morvinski, Coby; Shoham, Meyrav; Kyung, Ellie J (Journal of Consumer Research, 2026)
Abstract Consumers’ choices of whom to follow on digital platforms shape their informational landscape. In an era in which the credibility of informational sources is critical, this research examines two key questions: (1) When do consumers prioritize communicator credibility over likability in their decisions to follow? and (2) How do multiple credibility and likability cues interact to influence these decisions? Analyzing four large datasets from popular following-enabled platforms, we find that consumers’ orientation toward content consumption—goal directed (“search”) versus experiential (“scroll”)—is key. Communicator credibility drives following on search-driven platforms (Yelp, Goodreads), whereas likability drives following on scroll-driven ones (Twitter/X, Instagram). Aggregate communicator sentiment across multiple posts serves as a cross-platform indicator of credibility and likability, and its effect on follower count differs by platform type. On scroll-driven platforms, communicators with positive aggregate sentiment benefit from a likability premium, attracting the most followers; this preference for positivity is mitigated by the presence of alternative communicator likability cues (e.g., using sociable language). On search-driven platforms, communicators with mixed aggregate sentiment benefit from a credibility premium, attracting the most followers; this preference for mixed sentiment is mitigated in the presence of alternative credibility cues (e.g., Yelp’s “Elite” badge). Implications for consumer protection and platform design are discussed.